An Expert Panel Statement on the Beneficial Effects of Human Milk Oligosaccharides (HMOs) in Early Life and Potential Utility of HMO-Supplemented Infant Formula in Cow's Milk Protein Allergy - Sekerel, Bulent Enis; Bingol, Gulbin; Cokugras, Fugen Cullu; Cokugras, Haluk; Kansu, Aydan; Ozen, Hasan; Tamay, Zeynep (DOVE MEDICAL PRESS LTD, 2021)
This review by pediatric gastroenterology and allergy-immunology experts aimed to address the biological roles of human milk oligosaccharides (HMOs) and the potential utility of HMOs in prevention of allergy with particular emphasis on cow's milk protein allergy (CMPA). The participating experts consider HMOs amongst the most critical bioactive components of human milk, which act as antimicrobials and antivirals by preventing pathogen adhesion to epithelial cells, as intestinal epithelial cell modulators by enhancing maturation of intestinal mucosa and intestinal epithelial barrier function, as prebiotics by promoting healthy microbiota composition and as immunomodulators by modulating immune cells indirectly and directly. Accordingly, the participating experts consider the proposed link between HMOs and prevention of allergy to be primarily based on the impact of HMO on gut microbiota, intestinal mucosal barrier, immunomodulation and immune maturation. Along with the lower risk of respiratory and gastrointestinal infections, HMO supplemented formulas seem to be promising alternatives in the management of CMPA. Nonetheless, the effects of individual as well as complex mixtures of HMO in terms of clear clinical and immunological effects and tolerance development need to be further explored to fully realize the immunomodulatory mechanisms and the potential for HMOs in prevention of allergic diseases and CMPA.
Keywords: human milk oligosaccharides; gut microbiota; intestinal mucosal barrier; infant formula; immune tolerance; cow's milk protein allergy